Prophylactic antibiotics for manual removal of retained placenta during vaginal birth: a systematic review of observational studies and meta-analysis - Chibueze, Ezinne C. (BMC Pregnancy Childbirth, 2015)
BACKGROUND: Manual removal of the placenta is an invasive obstetric procedure commonly used for the management of retained placenta. However, it is unclear whether antibiotic prophylaxis is beneficial in preventing infectious morbidity. We conducted a systematic review to determine the efficacy and safety of routine use of antibiotics for preventing adverse maternal outcomes related to manual placenta removal following vaginal birth. METHODS: A detailed search of MEDLINE, EMBASE, Cochrane library and the CINAHL databases was conducted for non-randomized studies involving women undergoing manual placenta delivery after vaginal births and where antibiotic prophylaxis use was compared with no treatment or placebo to prevent maternal infection. Search terms including ‘delivery, obstetric’, ‘placenta, retained’, ‘anti-infective agents’, and ‘chemoprevention’ were used. RESULTS: Of the 407 citations that resulted after elimination of duplicates, 81 full texts were potentially eligible after independent assessment of the title and abstracts. Independent review of the full texts identified three eligible cohort studies which were retrospective in design. These studies contained data on two of the pre-specified outcomes, endometritis and puerperal fever. Other secondary outcomes such as perineal infection and/or any infection, hospital stay duration, sepsis, hemorrhage >1000 ml or hospital readmissions were not reported on excluding puerperal fever. A meta-analysis showed no significant reduction in the incidence of endometritis (odds ratio [OR] 0.84, 95 % confidence interval [CI] 0.38 to 1.85, three studies, 567 women) and puerperal fever (OR 0.99, 95 % CI 0.38 to 2.27, one study, 302 women). CONCLUSIONS: There is currently no evidence to suggest beneficial effects for routine antibiotic use in women undergoing manual placental removal following vaginal birth. In appropriate settings, further research is required to determine whether a policy of routine antibiotic prophylaxis for the procedure should be maintained or discouraged.